Comparison of Drug Control Strategies in San Diego, 1989 - Pennell, Susan ([Verlag nicht ermittelbar], 1993)
This study assesses the consequences for offenders of various drug enforcement strategies employed by the San Diego Police Department and profiles the factors that characterize street-level and mid-level dealers, drug users, and the drug market. The drug enforcement strategies examined include the use of search warrants, body wires, police decoys, surveillance, officer buys and sells, wiretaps, and sweeps. Measures of the consequences of arrests include drug and property seizures, convictions, and sentences. The data were drawn from police and court records of drug arrests made by three special sections of the police department in San Diego, California. Additionally, data were collected through personal interviews conducted at the time of arrest with a subsample of persons arrested for drug charges. The arrest tracking file, Part 1, contains demographic information about the offenders, including criminal history and gang membership, as well as data on each arrest through final disposition, charges, and sentencing. The interview portion of the study, Part 2, provides information about the demographics and characteristics of drug users and dealers, criminal history and drug use history, current arrest information, and offenders' opinions about drug use, drug sales, police strategies, and the drug market.